Impact of Socioeconomic Factors and Health Insurance Coverage on Out-of-Pocket Health Expenditure among Ghanaian Women: Implications for Health Financing Policy - Michael Ekholuenetale; Chimezie Igwegbe Nzoputam; Charity Ehimwenma Joshua; Amadou Barrow (Advances in Public Health)
Background. The cost of health financing is an age-long social challenge in resource-constrained settings. Out-of-pocket (OOP) health spending adversely affects maternal healthcare provisions and use, making health insurance one of the most effective social interventions. Objective. The purpose of this research was to study the effect of OOP health expenditure on socioeconomic factors and health insurance coverage among Ghanaian women. Materials and Methods. Secondary statistical data pulled out from Ghana Demographic and Health Survey (GDHS)—2014 was investigated. A sample of 9,396 women whose ages ranged from 15 to 49 years was studied. We used marginal predictive model to examine the interaction effect between socioeconomic factors and health insurance coverage on OOP health expenditure. The significance level was determined at 5%. Results. Overall, about 41.9% (95% CI: 39.4%−44.4%) of Ghanaian women reported OOP health expenditure for drugs and services. Amongst those covered by health insurance, this was 37.9% (95% CI: 35.3%−44.4%). The marginal interaction effects of OOP health expenditure were higher for women in the lowest neighborhood socioeconomic disadvantage group (42.6%) than those in the highest neighborhood socioeconomic disadvantage group (26.0%) who were covered by health insurance. In addition, the marginal interaction effects of OOP health expenditure were found to be greater among women who had higher education (43.8%) compared with those who had no formal education (34.0%) who were covered by health insurance. Furthermore, the marginal interaction effects of OOP health expenditure were higher for rural (39.0%), than their urban counterpart (36.6.0%) who were under the covering of health insurance. Conclusion. There is a gap in health insurance coverage, which leads to increased OOP health expenditure. The OOP health expenditure effect was more concentrated among high socioeconomic women with health insurance. The healthcare system’s stakeholders should implement policies aimed at eliminating OOP health expenditure for maternal health services.